Implementation of the Family Hope Program to Improve Community Welfare - Asriadi, Asriadi; Herman, Herman; Yunus, Andi Muhammad; Mardi, Mardi; Muslimin, Muslimin (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The Family Hope Program (PKH) is directed towards a group of family-oriented systematic social assistance programs. The aim of this research is to examine the implementation of the Family Hope Program (PKH) in an effort to improve community welfare and to identify factors that support and hinder its implementation in Lampoko Village, Barebbo District, Bone Regency. This research uses a quantitative approach by collecting data through a survey using a structured questionnaire to a random sample of PKH beneficiary families in the village. The sampling technique used was stratified random sampling with a survey population of 293 families in Lampoko Village. The research results show that the Family Hope Program (PKH) has had a positive impact in improving the welfare of the community in Lampoko Village, Barebbo District, Bone Regency, although it still faces several challenges in its implementation. This research highlights the importance of updating accurate data, increasing efficiency in aid distribution, and adjusting aid according to the actual needs of recipient communities. This program can be used as a reference for similar programs in other areas, with recommendations to continue to carry out continuous evaluation and improvement to maximize the benefits provided to deserving communities